Early onset age increases the risk of musculoskeletal damage in patients with type 2 diabetes - Zheng, Biao; Zhang, Yongze; Huang, Lingning; Shen, Ximei; Zhao, Fengying; Yan, Sunjie (Frontiers in Endocrinology, 2023)
Introduction: It's not clear whether there are differences in musculoskeletal damage and body composition among different age groups of type 2 diabetes.Therefore, the purpose of this study is to analyze the difference between early-onset type 2 diabetes (EOT2D) and non-early-onset type 2 diabetes (NOT2D) in musculoskeletal damage.Methods: A total of 964 patients with type 2 diabetes mellitus were selected by 1:1 propensity score matching, including 534 males and 430 females, with an average age of 52 ±7 years and an average course of 10 ±8.5 years. Bone mineral density and body composition were measured, and combined with biochemical tests, linear regression and binary logic regression were used to analyze the relationship between EOT2D, NOT2D and musculoskeletal damage. In addition, 414 patients with T2DM were selected according to whether they were hospitalized twice or not, and the median follow-up period was 44 months. COX survival analysis further elucidates the relationship between EOT2D, NOT2D and musculoskeletal damage.Results: Compared with patients with non-early-onset type 2 diabetes, A/G was negatively correlated with the age of onset, and had statistical significance. EOT2D has a higher risk of sarcopenia, osteoporosis and even musculoskeletal damage. With the prolongation of the course of the disease, the risk of muscle mass and/or bone mineral density decrease in EOT2D increases.Conclusions: EOT2D brings a greater risk of sarcopenia and/or osteoporosis, as well as a higher risk of reduced ASM and BMD. In addition, fat distribution may be more central.